Exploring possible transition ways for the use of hydrogen as an energy source in the Brazilian Electric Power Sector - Macedo, Sabrina Fernandes (2022)
The next step of the global energy transition will probably be based on the hydrogen economy in order to guarantee a sustainable future. Therefore, this study examines the possibilities for expanding the hydrogen market in the Brazilian electric power sector in a model that will contribute to the country taking full advantage of competitive features. Thus, this work is divided into two articles which answer this main goal. The first paper analyzes the economic feasibility of renewable hybrid systems for hydrogen production and storage in the Brazilian electric power sector. Thus, to evaluate this proposal, the methodology used is based on economic cost analyses of the two largest wind and solar photovoltaic plants in the country. In conclusion, it was found that the number of hours of electricity available for hydrogen production directly influences its cost. However, fully dedicated plants producing green hydrogen have shown economic feasibility when the hydrogen is exported or used in other sectors, so trading hydrogen was found more profitable than transforming it back into power. The model also concludes that wind and solar hybrid systems for hydrogen production and storage are still not economically viable in Brazil. The second paper aims to assess countries with the most effective hydrogen strategies, bringing up lessons for Brazil. This work\'s main question is how Brazil can accelerate its hydrogen economy. To answer this question, the methodology applied is based on identifying policy front-runners and potential leading markets, where three countries were selected: Germany, Netherlands and Australia. Then, the analysis was carried out first by outlining six pillars that are supporting countries to thrive in the hydrogen market. Then a survey was conducted to gather enough information on how the selected countries are engaging in each pillar. Finally, a critical analysis is conducted to sort out lessons to learn for Brazil. It was found that: (i) Brazil must establish a regulatory framework providing legal and regulatory security to investors; (ii) the Brazilian government should promote strong public polices; (iii) Brazil shall make concrete alliances with front-runners countries; (iv) renewable potential is not the only factor that determines high potential hydrogen producers, factors like existing infrastructure, soft factors (e.g. government support, businesses friendliness, political stability) and potential demand for hydrogen, are also major determinants. Finally, a discussion will be made covering the results extracted from the two papers, pointing out the characteristics that Brazil has as favourable to achieving a Hydrogen-based economy and essential requirements to enable the grow of hydrogen production, cooperating in the transition to a low-carbon economy.